Environmental policy and the macroeconomy under shallow-lake dynamics - Ben J. Heijdra; Pim Heijnen (Center for Economic Studies and ifo Institute (CESifo), 2009)
We study the environmental and economic effects of public abatement in the presence of multiple stable steady-state ecological equilibria. Under shallow-lake dynamics (SLD), the isocline for the stock of pollution features two stable branches, a good and a bad one. Assuming that the ecology is initially located on the upper (bad) branch of the isocline, the ecological equilibrium is hysteretic and a suitably designed temporary abatement policy can be used to steer the environment from the bad to the good equilibrium. In all models considered in this paper, a cold turkey abatement policy is optimal, i.e. the largest feasible shock should be administered for the shortest possible amount of time. Depending on the particular model used to characterize the economic system, there is a capital feedback effect that either helps or hinders the attainment of a successful abatement policy.
Keywords: D60; E62; H23; H63; Q20; Q28; Q50; 330; Shallow-lake dynamics; bifurcation; environmental policy; abatement; overlapping generations; Umweltpolitik; Umweltauflage; Schock; Wirkungsanalyse; Umweltökonomik; Nichtlineare dynamische Systeme; Gleichgewicht; Mehr-Sektoren-Modell; Overlapping Generations; Theorie